Bulk wave transmission by a multistrip coupler (MSC) - DANICKI, E. (Archives of Acoustics, 1998)
Multistrip coupler (MSC) is a component of SAW devices that couples surface acoustic waves (SAWs) propagating in two acoustic channels on piezoelectric substrate. Little is known in SAW literature about simultaneous transmission of bulk waves by MSC; it is beliewed that MSC efficiently suppress bulk wave spurious signals in SAW devices, and this is one of reasons of application of MSC in SAW devices. In this paper we investigate the efficiency of bulk wave transmission by MSC. New theory of MSC is developed that accounts for the fact that MSCs comprise finite number of conducting strips spanning over two acoustic channels. Numerical analysis based on FFT algorithm shows that bulk waves can be quite efficiently transmitted by MSC. This means particularly, that MSC can be applied to couple the surface skimming bulk waves which, having large velocity, are attractive for higher frequency SAW devices. In this case, MSCs would make it possible to shape the device frequency response by two apodized interdigital transducers (IDTs) converting electric signal to ultrasonic surface waves.